Associations Between Performance on the Entrance Exam and Subsequent Academic Performance at the Federal University of Minas Gerais - Golgher, André Braz (Revista Brasileira de Sociologia - RBS, 2020)
This paper analyses associations between performance on the entrance exams and subsequent academic performance at the Federal University of Minas Gerais (UFMG). Results clearly indicate that minority students catch up with other students while attending the university. For those who entered this institution in 2009, when the first stage of the selection process was UFMG´s own exam, the Portuguese, Mathematics, and Science exams had a larger predictive power, while the humanities and foreign language exams showed non-significant results or played smaller roles in predicting GPA outcomes. For those who were selected in the entrance exam of 2012, when the National Exam of the Secondary Level (ENEM) was used as the first stage of the selection process, all four exams (Language, Mathematics, Humanities, and Science) showed positive and significant results. In addition, the second stage of UFMG´s exam had a greater predictive power when ENEM was used as the first stage of the selection process.